B-cell non-Hodgkin's lymphoma in the patient with chronic hepatitis C and mixed cryoglobulinemia - V. S. Adonyeva; Ye. A. Kolodyazhnaya; A. B. Bochkarev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To describe clinical case of development B-cell non-Hodgkin's lymphoma (В-NHL) in the patient with chronic hepatitis C, to demonstrate potential of concurrent treatment of В-NHL and viral infection, regression of lymphoma on a background of antiviral therapy.Summary. Presented case shows development of B-cell non-Hodgkin's lymphoma in the patient with long-term infection of hepatitis C virus and autoimmune disorders, i.e. mixed cryoglobulinemia. Laboratory tests revealed moderate cytolytical activity: alanine transaminase (ALT) was 135 U/ml, aspartate aminotransferase (AST) —140 U/ml. Immunologic tests have confirmed the presence of HCV (RNA HCV — 15374 IU, genotype 1b). Abdominal US demonstrated signs of severe diffuse changes of the liver, pancreas, splenomegaly, signs of lymphadenopathy. Presence of mixed cryoglobulinemia within symptomatics of chronic HCV-infection, long history of infection were indicative of HCV-associated lymphoma development. Treatment: interferon-æ2b 3 million IU per day, ribavirin 1000 mg per day. On the 4-th week of treatment rapid virologic response (RNA HCV <16 U/ml), accompanied by biochemical remission (ALT 17 U/ml, AST 19 U/ml) was achieved. At US of the chest soft tissues and anterior abdominal wall no pathological mass lesions were revealed, at investigation of abdominal organs and retroperitoneum no lymph nodes were visualized.Conclusions. Rapid regression of foci lymphatic proliferation on a background of antiviral treatment (interferon-α2b combined to ribavirin) can serve as confirmation of HCV-infection role in lymphoma development and correlates to HCV suppression. Simultaneous antiviral treatment and polychemotherapy can be recommended at HCV-associated lymphomas.